2003
DOI: 10.1243/09544080360562972
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the tensile strength of caked sugar produced from humidity cycling

Abstract: The aim of this study was to develop moisture migration modelling in stored sugar due to the temperature cycling of the storage environment. This was done by forming cake of sugar in a gas-bearing tensile tester. The sugar and tester were enclosed in a controlled humidity system and the relative humidity was cycled between four hours at 70 per cent relative humidity and four hours at 20 per cent relative humidity. Liquid bridges formed between the sugar particles at high relative humidity, with the bridges har… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 6 publications
0
12
0
Order By: Relevance
“…The problem is thought to be related to the temperature gradients that induce the movement of moisture within the bulk sucrose (Bagster (1970a,b); Bagster and Ewing (1986); Bagster and Rizzo (1987); Leaper et al (2003); Ludlow and Aukland (1990); Purutyan et al (2005)) in a similar way to that shown by Bronlund and Paterson (2008) for bulk lactose. Fig.…”
Section: Introductionmentioning
confidence: 87%
“…The problem is thought to be related to the temperature gradients that induce the movement of moisture within the bulk sucrose (Bagster (1970a,b); Bagster and Ewing (1986); Bagster and Rizzo (1987); Leaper et al (2003); Ludlow and Aukland (1990); Purutyan et al (2005)) in a similar way to that shown by Bronlund and Paterson (2008) for bulk lactose. Fig.…”
Section: Introductionmentioning
confidence: 87%
“…Understanding the caking behavior of powders can be difficult when bulk powder properties are studied due to the many factors affecting caking and the complex interactions between individual particles [1][2][3]. In order to gain a greater understanding of the particles themselves and their properties, scanning electron microscopy (SEM) investigations have previously been used [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…The reasons for caking in sucrose have been well documented with the mechanism being identified as ''humidity caking", whereby powder exposed to high relative humidity air adsorbs water from the air which collects between the powder particles as a liquid due to capillary condensation and subsequently forming liquid bridges. The water dissolves some of the surface of the sugar and when conditions change and the water evaporates, a solid bridge is created between the particles, causing a solid cake to form (Bagster, 1970a,b;Bruijn et al, 1996;Irani et al, 1959;Leaper et al, 2003Leaper et al, , 2002Ludlow and Aukland, 1990;Mathlouthi and Roge, 2001;McGinnis, 1971;Meade, 1963;Moss et al, 1933;Nelson, 1949;Nichol, 1990;Pancoast and Junk, 1980;Pennington and Baker, 1990;Mathlouthi, 2000, 2003;Scoville and Peleg, 1981).…”
Section: Introductionmentioning
confidence: 99%
“…In order for these models to be useful, it is necessary that the relative humidity conditions that lead to significant levels of caking be established. Leaper et al (2003) used a tensile tester to measure the strength of particle bridging that occurred when the relative humidity was cycled between 70% and 20% as a function of the number of cycles. No work was found in the literature relating the strength of caking formed from the humidity caking mechanism for lactose.…”
Section: Introductionmentioning
confidence: 99%